Sistem Penunjang Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode Analytical Hierarchy Process (AHP) - Silviliani, Ilun; Priyatna, Ade (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The best selection is made to give an award to employees who have worked well and are exemplary. This is done as a form of gratitude for what has been given to the company. However, in selecting the best employees there are several criteria for consideration, namely discipline, attendance, communication, cooperation and responsibility. Due to the large number of employee data, causing the decision-making process time. So, the author uses the Analytical Hierarchy Process method where the decision-making process is carried out by evaluating alternatives based on predetermined criteria to help speed up decision making in selecting the best employees. The alternative matrix calculation yields a value of 0.333 or 33,3% for employee 4 on behalf of Apri Yuliani. And those employees are recommended as the best employees